2022
DOI: 10.1021/acschemneuro.1c00741
|View full text |Cite
|
Sign up to set email alerts
|

Roles of VGLUT2 and Dopamine/Glutamate Co-Transmission in Selective Vulnerability to Dopamine Neurodegeneration

Abstract: Growing evidence has established that a subset of dopamine (DA) neurons co-release glutamate and express vesicular glutamate transporter 2 (VGLUT2). VGLUT2 expression in DA neurons plays a key role in selective vulnerability to DA neurodegeneration in Parkinson's disease (PD). In this review, we summarize recent findings on impacts of VGLUT2 expression and glutamate co-release from DA neurons on selective DA neuron vulnerability. We present evidence that DA neuron VGLUT2 expression may be neuroprotective, boos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…1–5 Similarly, little experimental information is available on the regulation and functional effects of co-transmission, a ubiquitous feature of the nervous system that presumably plays a vital role in controlling the death of neurons. Although it has been nearly 45 years since the concept of “co-transmission” was introduced, 6–10 most early studies have been performed with lower vertebrate model systems. More recent studies with optogenetics 11,12 reveal more accurate information related to higher vertebrate systems; 13,14 however, there are limitations associated with these measurements.…”
Section: Introductionmentioning
confidence: 99%
“…1–5 Similarly, little experimental information is available on the regulation and functional effects of co-transmission, a ubiquitous feature of the nervous system that presumably plays a vital role in controlling the death of neurons. Although it has been nearly 45 years since the concept of “co-transmission” was introduced, 6–10 most early studies have been performed with lower vertebrate model systems. More recent studies with optogenetics 11,12 reveal more accurate information related to higher vertebrate systems; 13,14 however, there are limitations associated with these measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane of the functionalized nanochannel with D‐Trp‐P5 as the host molecule is close to the distribution of the DA transporter (DAT) in the presynaptic membrane. [ 71 ] That endows the nanochannel with the function of fast transportation of DA. The functionalized nanochannels are capable of wettability recognition of DA and electricity‐wettability controlled fast transmission of DA in nanochannels ( Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on these or other works, it is often asserted that only few glutamate neurons are present in SNc and VTA cell groups, in stark contrast to many recent studies and the results reported here. Indeed, multiple studies highlight the functional relevance of VTA glutamate neurons in appetitive and aversive behaviors (Barbano et al, 2020;Qi et al, 2016;Warlow et al, 2023;Yoo et al, 2016;Zell et al, 2020), and endogenous VGLUT2 expression in SNc DA neurons confers resistance to neurotoxic insults (Buck et al, 2022;Dal Bo et al, 2008;Shen et al, 2018;Steinkellner et al, 2018Steinkellner et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…The ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) are critical structures for processing reward, motivation, learning, and movement. While dopamine (DA) neurons have received the most attention, VTA and SNc neurons that release GABA (γ-aminobutyric acid) or glutamate can mediate related functions and have been implicated in addiction and Parkinson’s disease (Barcomb & Ford, 2023; Buck et al, 2022; Morales & Margolis, 2017). Also present are neurons that co-express multiple neurotransmitter markers and that can release multiple neurotransmitters, supported by electrophysiological evidence demonstrating co-release of DA and glutamate, DA and GABA, or GABA and glutamate (Chuhma et al, 2004; Hnasko et al, 2010, 2012; Root et al, 2014; Stuber et al, 2010; Tecuapetla et al, 2010; Tritsch et al, 2012; Yoo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%